MUNICIPAL MANAGEMENT AND LOCAL GOVERNMENT IN RUSSIA: THEORY AND DEVELOPMENT PROSPECTS - O. Demenko; I. Makarova (Вестник университета)
The article considers the peculiarities of municipal management and local self-government system, the study of the prospects for development of the municipal government in the conditions of modern Russian reality. Considered the municipal level of government as an institution of government, influencing the qualitative improvement of the lives of citizens. Financial sustainability of municipalities, especially small for the number of settlements and municipal districts of the population, leading to problems in the formation of an innovative society.